Efficacy of direct oral anticoagulants on the resolution of left ventricular thrombus—A case series and literature review. (April 2019) - Bahmaid, Reem A; Ammar, Shoroq; Al-Subaie, Sarah; Soofi, Mohammed A; Mhish, Hassan; Yahia, Madonna Ali
Background: Left ventricular thrombus is a frequent complication of acute myocardial infarction and a risk factor for thromboembolic complications. Warfarin has been frequently used, but has some disadvantages that limit its use. Direct oral anticoagulants, in particular Dabigatran and Rivaroxaban have been proved to be effective in preventing thromboembolism among patients with non-valvular atrial ﬁbrillation. However, no randomized clinical trials testing the efficacy and safety of these agents in patients with existing left ventricular thrombus. Furthermore, direct oral anticoagulants are still not approved by the Food and Drug Administration in the management of left ventricular thrombus. Method: This study was a retrospective cohort assessing the efficacy of direct oral anticoagulants (Dabigatran or Rivaroxaban) on the resolution of left ventricular thrombus in patients taking either of these drugs during the study period from December, 2011 to December, 2016 at King Fahad Medical City. All patients' records were reviewed and all patients who were diagnosed with left ventricular thrombus were included. Patients without available echocardiogram records were excluded. The study was approved by the institutional review board of King Fahad medical city, Riyadh Saudi Arabia. Result: During the defined study period we found that 413 and 1218 patients were taking Dabigatran and Rivaroxaban, respectively. After filtering them based on the specialty of the prescriber, we ended up with 299 patients who have been started on Dabigatran and 448 patients who have been started on Rivaroxaban by cardiologists. Moreover, after reviewing echocardiogram reports for all of them (747 patients), we found that 11 patients were diagnosed to have left ventricular thrombus. Among those 11 patients, seven of them were treated with direct oral anticoagulants from the beginning and the remaining four patients were shifted from Warfarin to direct oral anticoagulants. All of them (7 patients) showed left ventricular thrombus resolution on follow-up echocardiogram. Conclusion: Use of direct oral anticoagulants showed promising results in the resolution of left ventricular thrombus in patients diagnosed with left ventricular thrombus. Further studies at multiple health care centers are needed to further evaluate the efficacy and safety of direct oral anticoagulants as compared to traditional treatment in patients with left ventricular thrombus.